Supervisi Akademik Berbasis Bukti: Tinjauan Filosofis Realisme Dalam Praktik Pengajaran - Saifuddin Helmi; Arif Rifa’i; Agus Darmuki; Mohammad Kanzunnudin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Academic supervision is a crucial pillar in ensuring the quality of education, which currently tends to be administrative and normative in nature, falling short of the professional idealism grounded in empirical evidence. This study aims to analyze the gap between the concept of evidence-based academic supervision and its actual implementation in the field, particularly in elementary schools in Sukolilo District, and to examine the relevance of the philosophical foundation of realism. Using a descriptive qualitative approach, this study employs library research and field studies through observation, interviews, and document analysis in 40 elementary schools in the Sukolilo District. The findings show that 80% of supervision in Sukolilo still focuses on administrative document checks without classroom observation or data-based pedagogical feedback, creating anxiety among teachers and hindering improvements in teaching quality.  . Supervisi akademik merupakan pilar penting dalam penjaminan mutu pendidikan yang saat ini masih cenderung bersifat administratif dan normatif, jauh dari idealisme profesional berbasis bukti empiris. Penelitian ini bertujuan untuk menganalisis kesenjangan antara konsep supervisi akademik berbasis bukti dengan praktik di lapangan, khususnya di Sekolah Dasar Kecamatan Sukolilo, serta relevansi landasan filsafat realisme. Menggunakan pendekatan kualitatif deskriptif, studi ini menerapkan metode studi pustaka dan studi lapangan melalui observasi, wawancara, dan analisis dokumen di 40 Sekolah Dasar di Kecamatan Sukolilo. Hasil penelitian menunjukkan bahwa 80% supervisi di Sukolilo masih berfokus pada pemeriksaan dokumen administratif tanpa observasi kelas atau umpan balik pedagogis berbasis data, menciptakan kecemasan bagi guru dan menghambat perbaikan kualitas pembelajaran.